1980
DOI: 10.1159/000131439
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the determinants of nuclear pore number

Abstract: To assess the functional significance of nuclear pore complexes, we have investigated whether the number of pores per nucleus is determined by such factors as the nuclear volume, nuclear surface area, DNA content, or aspects of nuclear activity. Comparisons were made between cell types chosen to permit observation of differences in nuclear pore number as a function of differences in the other qualities measured. The number of nuclear pores was determined by freeze-etching and measurements of nuclear surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 5 publications
4
31
0
Order By: Relevance
“…The data showed that the number of NPCs is not directly proportional to the DNA content but to the nuclear surface which in the 4n is only 1.6 times larger than in the 2n. This fact suggested that the number of NPCs could be related to transcription activity or to the transport of products to the cytoplasm (Maul et al 1980). The intranuclear fi laments here described in both 2n and 4n species assemble in a network that connect NPCs and are associated with chromatin fi bers, spheroidal structures and RNP particles.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The data showed that the number of NPCs is not directly proportional to the DNA content but to the nuclear surface which in the 4n is only 1.6 times larger than in the 2n. This fact suggested that the number of NPCs could be related to transcription activity or to the transport of products to the cytoplasm (Maul et al 1980). The intranuclear fi laments here described in both 2n and 4n species assemble in a network that connect NPCs and are associated with chromatin fi bers, spheroidal structures and RNP particles.…”
Section: Discussionmentioning
confidence: 70%
“…A possible difference among these species is the common presence of aggregates of pores connected by intranuclear fi laments in the tetraploid animals. Previous data showed that the frequency of clusters with four pores increases in these polyploid anurans (Maul et al 1980). We do not know whether the complex aggregates of neighboring NPCs associated with the intranuclear fi laments obtained in the spreads might correspond to the pore clustering described in these 4n frogs using freeze-etching experiments (Maul et al 1980).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although overt changes in nucleocytoplasmic trafficking will dramatically affect cellular homeostasis, it is unclear whether subtle stimuli can sufficiently alter transport to effect physiological and pathological changes in cell growth. Although metabolism plays an important role in modifying nuclear protein import (31), it currently remains unknown whether a lipid metabolite can inhibit nuclear transport. This suggestion was based upon an association of nuclear pore density with cellular transcriptional capacity and "release of products to the cytoplasm" (31).…”
mentioning
confidence: 99%